(untitled) (Tempo e Argumento, 2021)
The activities of voluntary whistleblowers and collaborating informants during the Military Dictatorship in Brazil (1964-1985) are investigated. Letters and memos sent by several common people to security departments and political police informing on political adversaries, neighbors, co-workers and friends are analyzed. The documents under investigation have been retrieved from the DOPS archives at the State Department of the Public Archives of the State of Paraná (DEAP). Whistleblowing was a very common practice during the Military Regime and informants had an important role conniving with the regime´s security organs within the vigilance and social control process of the Brazilian population